The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1016/j.expneurol.2006.01.030
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory ensheathing cells, olfactory nerve fibroblasts and biomatrices to promote long-distance axon regrowth and functional recovery in the dorsally hemisected adult rat spinal cord

Abstract: Cellular transplantation, including olfactory ensheathing cells (OEC) and olfactory nerve fibroblasts (ONF), after experimental spinal cord injury in the rat has previously resulted in regrowth of severed corticospinal (CS) axons across small lesion gaps and partial functional recovery. In order to stimulate CS axon regrowth across large lesion gaps, we used a multifactorial transplantation strategy to create an OEC/ONF continuum in spinal cords with a 2-mm-long dorsal hemisection lesion gap. This strategy inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(43 citation statements)
references
References 49 publications
0
43
0
Order By: Relevance
“…Examples include: (a) the source of the tissue: olfactory bulb (OB), (Li et al, 1997;Ram on-Cueto et al, 1998), olfactory mucosa or lamina propria (LP); (Au and Roskams, 2002;F eron et al, 1999), (b) the age of the donor [adult, neonatal, or fetal; (Barnett and Roskams, 2008;Huang et al, 2008)], (c) the time in tissue culture (Garcia-Escudero et al, 2010a;Llamusi et al, 2010;Novikova et al, 2010), (d) whether the OECs are purified [in most studies, e.g., (Barnett and Chang, 2004;Chuah and Au, 1993)], or used as mixed primary cultures (Deumens et al, 2006;Raisman and Li, 2007;Yui et al, 2011), or cell lines (Garcia-Escudero et al, 2010b), (e) the use of growth factors (Bianco et al, 2004;Pollock et al, 1999), (f) the species: apart from the rat, other OECs have been prepared from mouse , pig (Radtke et al, 2004), dog (Ito et al, 2006), monkey (Guest et al, 2008), and human (Barnett et al, 2000;F eron et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Examples include: (a) the source of the tissue: olfactory bulb (OB), (Li et al, 1997;Ram on-Cueto et al, 1998), olfactory mucosa or lamina propria (LP); (Au and Roskams, 2002;F eron et al, 1999), (b) the age of the donor [adult, neonatal, or fetal; (Barnett and Roskams, 2008;Huang et al, 2008)], (c) the time in tissue culture (Garcia-Escudero et al, 2010a;Llamusi et al, 2010;Novikova et al, 2010), (d) whether the OECs are purified [in most studies, e.g., (Barnett and Chang, 2004;Chuah and Au, 1993)], or used as mixed primary cultures (Deumens et al, 2006;Raisman and Li, 2007;Yui et al, 2011), or cell lines (Garcia-Escudero et al, 2010b), (e) the use of growth factors (Bianco et al, 2004;Pollock et al, 1999), (f) the species: apart from the rat, other OECs have been prepared from mouse , pig (Radtke et al, 2004), dog (Ito et al, 2006), monkey (Guest et al, 2008), and human (Barnett et al, 2000;F eron et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, OECs are pluripotent cells that can show Schwann cell-like properties (5). When transplanted into the demyelinated spinal cord, OECs can repair the defective myelin and restore conductance in remyelinated axons (6)(7)(8). Although much is known about OECs, few studies have focused on the characteristics of ONFs, which are flat and compact cells forming multiple layers with thin processes encircling OECs (2).…”
Section: Introductionmentioning
confidence: 99%
“…They are biocompatible and biodegradable, and their mechanophysical properties (and thus the rate and timing of degradation) can be modulated to some degree (SakiyamaElbert et al, 2012). However, several studies have reported undesired effects or a lack of success that might be explained by the rate of degradation and a loss of structural support (Deumens et al, 2006;Hurtado et al, 2006).…”
Section: Lactide-and Glycolide-derived Polyestersmentioning
confidence: 99%